Investigating laboratory parameters of the resistance of different mixtures of soil – lime – fume using the curing and administrative method - Mahmoud Nematzadeh; Panam Zarfam; Mehdi Nikoo (Case Studies in Construction Materials, 2017)
Soils treatment is affected by various factors such as density, moisture content and mineral composition of soil and different percentages of materials in soil. Lime soil as a suitable and inexpensive material has been used for decades to stabilize in civil engineering projects; however, the effect of adding fume and curing temperature on strength and stability parameters of the mixture seldom been studied. In this study, soil and water has been studied from Dokhtar Borji in Hosseinieh city in Iran. Based on a laboratory study, we dealt with evaluating the physical and mechanical properties of soils and chemical properties of soil and water. The cylindrical samples of different mixtures of soil- lime- fume were modified using the AASHTO method and compressive strength testing of 7-, 14- and 28-day samples were conducted according to ASTM standards at 27 °C. Analysis was conducted in SAS (Statistical Analysis System) software. Results indicated that the increase in average compressive strength from 7 to 14 and from 14 to 28 days were 62 and 53.57%, respectively. Therefore, by increasing the number of curing days from 7 to 14, the percentage of the compressive strength is at its highest. The study also provided a linear regression equation that determines compressive strength with an accuracy of 95.1%.